Disrupting the neoliberal discourse of teacher reflection through dialogical-phenomenological texts. Issue 5 (3rd September 2019) - Sulzer, Mark A.; Dunn, Mandie B.
ABSTRACT: In this article, we explore the propensity for the neoliberal discourse of education to constrain reflective practice within teacher education programs (TEPs) and the potential for disrupting this neoliberal discourse by taking up concepts of dialogism and phenomenology. To pursue this goal, we developed a dialogical-phenomenological approach to teacher reflection. A dialogical-phenomenological approach to teacher reflection takes up lived experience as central to reflective practice and provides space for exploration through dialogue. Using examples from two TEPs, we describe two methods for enacting dialogical-phenomenological reflection: ahorizonalization method and a genre progression method. We found that a dialogical-phenomenological approach to reflection allowed for the creation of texts that (a) invited a range of teaching experiences into our discussions that were not reducible or resolvable but nonetheless crucial in building an understanding of teaching as implicated in social, cultural, and historical processes, and (b) invited preservice teachers to take a critical stance on the forces that structure their lived experiences in the classroom.